2014
DOI: 10.3150/13-bej538
|View full text |Cite
|
Sign up to set email alerts
|

The generalized Pareto process; with a view towards application and simulation

Abstract: In extreme value statistics, the peaks-over-threshold method is widely used. The method is based on the generalized Pareto distribution characterizing probabilities of exceedances over high thresholds in R d . We present a generalization of this concept in the space of continuous functions. We call this the generalized Pareto process. Differently from earlier papers, our definition is not based on a distribution function but on functional properties, and does not need a reference to a related max-stable proces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 11 publications
0
130
0
Order By: Relevance
“…Brown-Resnick processes: extremal increments of the process allow to work with a complete likelihood function (Engelke et al, 2015;Wadsworth and Tawn, 2014). A direct modeling of the exceedances of a max-stable process is also possible using a generalized Pareto process (Ferreira and de Haan, 2014) but such an approach is only of interest in the case of asymptotic dependence.…”
Section: Model Inferencementioning
confidence: 99%
“…Brown-Resnick processes: extremal increments of the process allow to work with a complete likelihood function (Engelke et al, 2015;Wadsworth and Tawn, 2014). A direct modeling of the exceedances of a max-stable process is also possible using a generalized Pareto process (Ferreira and de Haan, 2014) but such an approach is only of interest in the case of asymptotic dependence.…”
Section: Model Inferencementioning
confidence: 99%
“…de Haan and Lin (2001), Part III of de Haan and Ferreira (2006), Einmahl and Lin (2006) and Ferreira and de Haan (2014). For the theory presented here, the main difference between the R m setting and the C b (K) setting is that in the latter, exponential tightness of {P (Y/y ∈ ·), y > 0} no longer follows from the exponential marginals; it is an independent assumption.…”
Section: Discussionmentioning
confidence: 99%
“…A generalized Pareto process is defined as μ(s ) + σ (s )[Y ∞ (s ) ξ (s ) − 1]/ξ (s ) for the spatially varying location, scale, and shape parameters μ(s ), σ (s ) > 0, and ξ (s ), respectively; the case ξ (s ) = 0 is treated as ξ (s ) → 0. Ferreira & de Haan (2014) have shown that these processes arise as limits as n → ∞ for the rescaled process [Y (s ) − b n (s )]/a n (s ), conditional on there being at least one exceedance of some threshold u. Therefore, unlike max-stable processes, they provide a valid approximation to the upper tail when at least one variable is large.…”
Section: Pareto Processesmentioning
confidence: 95%
“…This approximation is justified when all variables are large; when not all variables are large, a censored likelihood approach may be adopted (see, for example, Huser & Davison 2014). The second is to use Pareto processes (Ferreira & de Haan 2014, Thibaud & Opitz 2014, recently introduced as the process analog of the GPD. In the same vein as Equation 25, a standard Pareto process can be defined as follows:…”
Section: Pareto Processesmentioning
confidence: 99%